Agricultural soil reclamation and restoration of soil organic matter and nutrients via application of organic, inorganic and bio fertilization (Mini review). Issue 1 (June 2021) - Imran; Amanullah; Hussain, I; Ali, I; Ullah, S; Iqbal, A; -Al Tawaha, A R; Al-Tawaha, A R; Thangadurai, D; Sangeetha, J; Rauf, A; Saranraj, P; et al.
Abstract: Food security is directly related to the ability of the land to support the population. Causes for land degradation are numerous and include the decline of soil fertility, development of acidity, salinization, alkalization, deterioration of soil structure, accelerated wind and water erosion, loss of organic matter and biodiversity. Thereafter, it is of critical importance to increase soil health and restore degraded soils in order to achieve sustainable development. Restoring the soil quality for crop production through the appropriate soil management and conservation techniques is important for all nations, primarily those at risk with respect to food security. Soil organic matter (SOM) plays a central role in maintaining soil functions and preventing soil degradation. Both organic matter and microorganism serve as a reservoir of plant nutrients. This study concluded that soil organic carbon and other mineral and nutrients restoration were noted with the soil modification and incorporation of various organic amendments. Plant residues and field biomass were promising for nutrients replenishment while biochar was the key component for the enrichment of soil organic carbon. Animal-based residues and manure application enhanced soil mineral and micronutrients concentration with the advantage of soil reclamation and restoration.